The complete mitochondrial genome of Leiolepis reevesii (Sauria, Agamidae). (2nd January 2016) - Tong, Qing-Lin; Du, Yu; Lin, Long-Hui; Ji, Xiang
Abstract: In this paper, we report the complete mitochondrial genome of Leiolepis reevesii (Sauria, Agamidae), which is a circular molecule of 16, 908 bp in size and consists of 13 protein-coding genes, 2 ribosomal RNAs, 22 transfer RNAs and a control region. The A+T content of overall base composition of H-strand is 59.8% (T: 25.1%, C: 27.5%, A: 34.7%, G: 12.7%). Some short microsatellite-like repeat regions (polyA and polyT) are scattered in the control region. All the results provide powerful data to further study of the molecular systematics, species identification and conservation genetics.